Impact of coronary artery disease on contractile function and ventricular‐arterial coupling during exercise: Simultaneous assessment of left‐ventricular pressure–volume and coronary pressure and flow during cardiac catheterization. Issue 10 (27th May 2021) - Patterson, Tiffany; Rivolo, Simone; Burkhoff, Daniel; Schreuder, Jan; Briceno, Natalia; Williams, Rupert; Arri, Satpal; Asrress, Kaleab N.; Allen, Christopher; Joseph, Jubin; McConkey, Hannah Z. R.; Ellis, Howard; et al.
Abstract: Coronary artery disease (CAD) can adversely affect left ventricular (LV) performance during exercise by impairment of contractile function in the presence of increasing afterload. By performing invasive measures of LV pressure–volume and coronary pressure and flow during exercise, we sought to accurately measure this with comparison to the control group. Sixteen patients, with CCS class >II angina and CAD underwent invasive simultaneous measurement of left ventricular pressure–volume and coronary pressure and flow velocity during cardiac catheterization. Measurements performed at rest were compared with peak exercise using bicycle ergometry. The LV contractile function was measured invasively using the end‐systolic pressure–volume relationship, a load independent marker of contractile function (Ees). Vascular afterload forces were derived from the ratio of LV end‐systolic pressure to stroke volume to generate arterial elastance (Ea). These were combined to assess cardiovascular performance (ventricular‐arterial [VA] coupling ratio [Ea/Ees]). Eleven patients demonstrated flow‐limiting (FL) CAD (hyperemic Pd/Pa <0.80; ST‐segment depression on exercise); five patients without flow‐limiting (NFL) CAD served as the control group. Exercise in the presence of FL CAD was associated impairment of Ees, increased Ea, and deterioration of VA coupling. In the control cohort, exercise was associated with increased Ees and improved VA coupling. The backward compression wave energy directly correlated with the magnitude contraction as measured by dP/dTmax ( r = 0.88, p = 0.004). This study demonstrates that in the presence of flow‐limiting CAD, exercise to maximal effort can lead to impairment of LV contractile function and a deterioration in VA coupling compared to a control cohort. Abstract : This invasive catheter laboratory exercise study in patients with ischemic heart disease demonstrated impairment of LV contractile function and deterioration in in VA coupling on maximal exercise in the presence of flow‐limiting coronary artery disease.